2022
DOI: 10.1002/admi.202102564
|View full text |Cite
|
Sign up to set email alerts
|

Toward Surfaces with Droplet Impact Robustness and Low Contact Angle Hysteresis

Abstract: the cavity bottom or reaches the local advancing contact angle. [19][20][21] To increase this critical velocity, the surface structure has to be designed such that it imposes a strong resistance to liquid impalement. Without changing the structure scale, this target can be realized by using a dense array of structures [19][20][21][22][23][24] or structures with special top to pin the liquid. For instance, sharp edge structures [25] can resist impalement better due to the additional pinning effect. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[19] In order to achieve high surface water-repellency, hydrophobic coating and roughness design are often applied. [12,20] However, surface water-repellency could be undermined when the Weber number of an impacting droplet exceeds a threshold, where the impact outcome transits from bouncing to wetting due to the Cassie-Wenzel transition. [21,22] The Cassie state refers to the scenario that air is trapped in the micro-structure beneath the droplet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19] In order to achieve high surface water-repellency, hydrophobic coating and roughness design are often applied. [12,20] However, surface water-repellency could be undermined when the Weber number of an impacting droplet exceeds a threshold, where the impact outcome transits from bouncing to wetting due to the Cassie-Wenzel transition. [21,22] The Cassie state refers to the scenario that air is trapped in the micro-structure beneath the droplet.…”
mentioning
confidence: 99%
“…[6][7][8] Experimental investigations of droplet impact on solid substrate revealed six identical modes, including deposition, partial bouncing, complete bouncing, receding breakup, prompt splash, and corona splash. [9] The outcome of droplet collision depends on various factors, such as droplet properties, [10] surface conditions, [11,12] ambient pressure, [13] and impacting angle and velocity. [14] Dimensionless numbers are used to characterize the droplet impact dynamics,…”
mentioning
confidence: 99%
“…[39][40][41] Ding et al suggested that compared with cylindrical pillar surfaces, appropriate design of the cone surfaces can resist liquid impalement without the increase the contact angle hysteresis. [42] However, these etched surfaces with ordered structure cannot be prepared in large area and have poor mechanical properties, it is difficult for them to meet the needs of engineering applications. [43,44] By contrast, disordered porous superhydrophobic surfaces prepared by one-step method show superior application prospect.…”
mentioning
confidence: 99%